Les parasitoses qui minent les nouveaux pôles de développement au Burkina Faso : cas des schistosomoses et des géohelminthes dans le complexe hydroagricole du Sourou - Poda Jean Noël; Mwanga Joseph; Dianou Dayéri; Garba Amadou; Ouédraogo François de Charles; Zongo Dramane; Sondo K. Blaise (VertigO)
The existing image in the Sahel Sudan Africa is often that of accelerated insecurity of plant and animal production conditions. Face with the growing hostility of nature, the people have for a long time adopted water and soil conservation strategies or migration. Thus, water development, especially the dam as an anthropic activity on the natural landscape, a notion linked to that of environmental and health risk seems to be a negotiable alternative, an answer to climatic vagaries. In Burkina Faso, the people want the construction of dams because, firstly, they provide water for man and animals, secondly, water provides food for man and animals. It is also used for dry season farming, irrigation, fishing and grazing. The satisfaction that the proximity of a dam gives is sufficiently felt by the people in all the regions, and today, small dams and hydro-agricultural developments which are often interrelated are more and more becoming part and parcel of the Burkinabe countryside.Under these conditions, the dams and farms are the new development poles aimed at solving the decreasing problem of food production per head which is the result of increasing population. However, these choices must not overshadow the numerous health risks associated with irrigation farming.Among the water-borne diseases; schistosomiasis and geohelminthis seem to be the most sensitive disease to changes in the relations between the human community and their aquatic environment, because one of their characteristic traits is their ability to adapt and benefit from the newly-created environment that resulted from the hydroagricultural development. There are several factors leading to their outbreak, their spread and the difficulty in controlling them among others: the framework of aquatic biotope, their juxtaposition in space, distribution and the development process of the number of the parasites, vectors and the intermediary hosts, movement of the human population with different lines of parasites and their state of immunity, the behaviour of man-man-water-parasite relations and the hygiene of the environment, the perception of the people about the disease, the therapeutic means, and consequently the pertinence of the IEC, the statue of women and children in the parasite transmission and treatment programme. It has been realised that hydro arming is one of the factors that enhance the proliferation of vectors of transmission and flux of parasite hosts. All the players, (land developers, the population and scientists) have been urged to use all the means at their disposal to alleviate or even stop the spread of the disease which is decreasing the expected agricultural returns.